Screening and surveillance of hereditary tumors in the Chiba Foundation for Health Promotion and Disease Prevention - Saitoh, Tomoko; Nomura, Fumio; Kitahashi, Nana; Fujisawa, Takehiko; Hashimoto, Hideyuki; Yamaguchi, Kazuya; Inada, Mari; Watanabe, Ayako (Journal of Hereditary Tumors, 2021)
Genomic and genetic health care is increasingly available in clinical practice. Since genetic services should play significant roles in preventive medicine as well, we established in Oct. 2015 the division of clinical genetics to effectively and carefully provide genetic services in the Chiba Foundation for Health Promotion and Disease prevention (CFHD), a non-profitable organization for health checkup and cancer screening for inhabitants and workers in Chiba prefecture. As a first step, we have tried to pick up subjects with hereditary tumors using cancer family history questionnaire among those having cancer screening and also through referrals of suspected cases from nearby hospitals. As of September 30, 2020, we have found five cases of Lynch syndrome and 4 cases of hereditary breast and ovarian cancer syndrome confirmed by genetic testing. Since cancer screening of multiple organs are well organized at CFHD, we have provided cancer screening and surveillance programs for their relatives as well. We are going to pursue “individualized cancer screening” based on genetic risk together with appropriate genetic counselling.